The Relationship between Caffeine Consumption Status and Happiness Levels of Students in the Faculty of Sports Sciences - Ezgi Samar,; Büşra Erul, (Journal of Educational Issues, 2024)
This study aimed to examine the relationship between the caffeine consumption status of students in sports sciences and their happiness levels. The study was quantitative and was conducted with the participation of 228 volunteer students studying in sports sciences from various universities (Artvin Coruh, Trabzon, Bayburt, Iğdır, Ağrı İbrahim Çeçen, Gazi, Atatürk). The Oxford Happiness Scale (OHS) developed by (Hills & Argyle, 2002) and this questionnaire were used to collect the data. Statistical analysis of the data was performed with independent groups T-test, one-way analysis of variance (ANOVA) and Pearson correlation analysis. As a result of the analysis, while a positive and low-level significant relationship was found between the students’ happiness scores and the age variable (p < .05); no significant difference was found in the variables of gender, body mass index (BMI), department of education (p > .05). When looking at the variable of doing sports, statistically significant differences were found, and it was concluded that the mean score of those who did sports as licensed-national was significantly higher than the mean score of those who did sports as hobbyists and amateurs (p < .05). Again, a statistically significant difference was found in happiness scores according to chronic disease states; (p < .05) no difference was found according to smoking status (p > .05). At the same time, a statistically positive and low-level significant relationship was found between happiness scores and the amount of coffee consumed daily (p < .05); No statistically significant relationship was found between happiness and the amount of black tea and chocolate consumed daily (p > .05).